OPTIMALISASI SUMBER DAYA DAN TEKNOLOGI DALAM PROGRAM PEMBERDAYAAN MASYARAKAT DESA PULAU JEMARE - Leksonowati, Nur Fitria Pujo; Pamungkas, Nurman; Butar, Hendra Butar; Aryswan, Adhe; Juangsa Putra, Lalu Giat; Fyona, Annisa; Nugroho, Cahyo Budi; Wibowo, Ari; Gemala, Mega; Ariyanto, Nugroho Pratomo; Arifin, Nurul Laili; Puspita, Roza; Sriyanto, Sriyanto; Dzulfiqar, Mohamad Alif; Stefani, Windy; Batubara, Ninda Hardina; Fajrin, Aulia; Purba, Adi Syahputra; Manurung, Meilani Mandhalena; Budiman, Budiman (Politeknik Negeri Batam, 2025)
This paper discusses in depth the implementation of the Village Community Empowerment Program (P2MD) carried out on Jemare Island. The main focus of this program is the application of appropriate technology, which includes public street lighting and a water pump system, both powered by solar panels. The main objective of this initiative is to improve the quality of lighting and the provision of clean water on the island, two important aspects that are greatly needed by the local residents. Through a series of intensive observations and discussions with the local residents, the community service team was able to identify and solve various problems faced by the residents. As a result of these efforts, four street lights have been successfully installed and operated, and the water pump system has been successfully connected to the water pump machine and water storage tank. It is hoped that this initiative can have a significant positive impact on the quality of life of the residents of Jemare Island, support their business activities and economy, and provide a solution to the uneven distribution of electricity by the state electricity company (PLN). This solution is practical because it utilizes renewable energy in the form of sunlight, which is abundantly available on Jemare Island.